Effects of traditional Chinese medicines on weight management among adults with overweight or obesity: A systematic review and network meta‐analysis - Meifang Chen; Jiaqi Liu (Wiley, 2024)
Abstract Increasing evidence has reported the anti‐obesity effects of traditional Chinese medicines (TCMs) and their potential advantages in weight loss, such as fewer side effects and lower costs compared to the current recommended treatments like Western medicines. Previous review studies have examined the effects of a few commonly used TCM therapies such as acupuncture and herbal medicines on weight loss. This network meta‐analysis (NMA) study aims to review and rank the effects of currently available TCMs on weight loss and to compare the effects of TCMs with different intervention durations. Eligible Randomized controlled trials (RCTs) conducted among Chinese adults with overweight or obesity were searched on electronic databases (PubMed, Embase, CNKI, WanFang, VIP, and SinoMed) up to 1 March 2023. Pairwise meta‐analysis was performed to examine the pooled effects of TCMs on weight loss, and NMA was conducted to rank different types of TCMs. Subgroup analysis stratified by intervention duration was performed. Forty‐six RCTs were eligible for inclusion in the review. The results showed that TCMs, especially when the treatment duration was ≤6 months, were more effective in both body weight and Body Mass Index (BMI) reduction than non‐pharmacological interventions and placebo/no treatment. Acupotomy was ranked as the most effective TCM treatment in reducing both body weight and BMI. Traditional Chinese medicines have promising potential for weight loss and could be included in future clinical guidance as a standalone or supplementary treatment for obesity. Future studies need to further investigate under‐researched TCMs, examine the long‐term effects and safety of TCMs in obesity treatment, and validate the findings from this study among other ethnic populations.